Physical Activity Behavior Predictors, Reasons and Barriers among Male Adolescents in Riyadh, Saudi Arabia: Evidence for Obesogenic Environment - Alsubaie, Ali Saad; Omer, Eltigani O.M. (International Journal of Health Sciences, 2015)
Objective: This study aimed to assess physical activity, socio-demographic predictors and to determine reasons for practicing and/or not practicing physical activities. Methods: Cross-sectional study was conducted among male high school students in Riyadh, Saudi Arabia. A self-administered questionnaire was used to collect the data using stratified cluster sampling technique (N= 453 students). Results: Although 36.4% of the student reported that they practiced enough exercise during their usual week days, only 15.5% of the students were found to be practicing physical activity at a recommended level (≥5 days/week). On the other hand, 20.1% of the students were found to be inactive and not practicing physical activity at any day. Among the factors that associated with adolescents physical activity, logistic regression showed that students age was associated negatively with physical activity behaviour (OR= 0.6, P <0.001). Also, logistic regression showed that students physical activity behaviour was independently associated with students perceived body weight (OR= 27, P <0.001). The main reasons for practicing physical activity were: to enhance muscle and strength (70.9%), to have fun with friend and entertainment (66%), and to improve physical appearance (53.6%), respectively. The main reported barriers inhibiting adolescents from practicing physical activity were: lack of sports facilities in the community (74%), lack of friends and peer support (59.4%) and lack of suitable public sport club in the community (54.6%). Conclusion: This study revealed low prevalence of physical activity among adolescents. National strategies to increase levels of physical activity and minimize obesogenic environmental factors are required.